Analysis of sanitation regionalization: Water scenarios and economic-financial (in)sustainability of the water and sewage microregions of Paraíba (Research, Society and Development, 2021)
On July 15, 2020, Federal Law No. 14,026 was published, amending a set of laws related to sanitation. This Law established a one-year deadline for the States to create a regionalization structure for sanitation, specifically for water and sewage services. If the states do not implement the water and sewage micro-regions within the established deadline, the sanitation regionalization will be established in a compulsory way by the Union, with the creation of reference blocks. Paraíba, through Complementary Law no. 168 (2021), created four micro-regions: Alto Piranhas, Borborema, Espinharas and Litoral. This article aims to analyze the technical feasibility and the economic-financial and environmental sustainability of these micro-regions. Indicators and information about the Paraíba municipalities made available by the National Sanitation Information System (SNIS), in 2015, 2017 and 2019, such as the financial performance indicator (IN012) and the cash sufficiency index (IN101), and the different water availability scenarios, through the monitoring data of the existing dams in these microregions, in 2015, 2017, 2019 and 2021, were analyzed. The main results and discussions revealed the economic-financial unsustainability of three microregions: Alto Piranhas, Borborema and Espinharas. The Microregion of Litoral, besides presenting more favorable climate conditions and concentrating more than 60% of the direct operational revenues of Paraíba, is the only one that presents economic-financial sustainability.